Pelaksanaan Konsep Merdeka Belajar pada Mata Pelajaran IPS di MTs Negeri 2 Medan - Lesma Yoana; Fatkhur Rohman; Silvia Tabah Hati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to find out: (1) planning for the implementation of the concept of independence in social studies subjects at MTs Negeri 2 Medan. (2) implementation of the concept of independence in social studies subjects at MTs Negeri 2 Medan. (3) evaluation of the implementation of the concept of independence in social sciences subjects at MTs Negeri 2 Medan. This research uses a qualitative approach with naturalistic methods, and the sample collection technique is carried out through purposive sampling. Data collection techniques were carried out through observation, interviews and documentation studies. Data analysis uses data collection techniques, data reduction, data presentation, and drawing conclusions. The data validity technique uses, (1) Credibility Test, (2) Transferability Test, (3) Dependability Test, (4) Corfirmability Test. The results of this research show: (1) Planning for the implementation of the independent learning concept in social studies subjects at MTs Negeri 2 Medan is going quite well. This is proven by providing outreach and training, creating learning tools, and conducting evaluations on teachers to ensure whether teachers are ready or not to implement the independent curriculum. (2) The implementation of the Independent Learning Concept at MTs Negeri 2 Medan was carried out quite well. Even though not all learning implementations are in accordance with the modules that have been created, this is because the independent curriculum is still very newly implemented at MTs Negeri 2 Medan, but the social studies teachers are quite creative and differentiated in making variations in teaching which makes students active, creative and critical. (3) Evaluation of the concept of independent learning in social studies subjects at MTs Negeri 2 Medan is going quite well as evidenced by data showing student scores above average based on the Learning Goal Achievement Kit (KKTP) at MTs Negeri 2 Medan.